2009
DOI: 10.1111/j.1471-4159.2009.05995.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone acts as a neuroprotectant in retinal cells via up‐regulation of sestrin‐1 and SOD‐2

Abstract: Rosiglitazone is a member of the thiazolidinedione family of synthetic peroxisome proliferator‐activated receptor (PPAR) agonists. It is a selective ligand of the PPARγ subtype and functions by regulating the transcription of insulin‐responsive genes. A screen of FDA‐approved compounds identified rosiglitazone as a novel anti‐apoptotic agent in retinal cells both in vitro and in vivo, functioning as a neuroprotectant in response to oxidative and calcium stress. We have found that the likely mechanism of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Among the top predictions, retinal disorders and glaucoma are also listed. It is reported that rosiglitazone is a potential neuroprotectant for retinal cells and may increase the retinal cell survival40. It may also delay the onset of proliferative diabetic retinopathy41.…”
Section: Resultsmentioning
confidence: 99%
“…Among the top predictions, retinal disorders and glaucoma are also listed. It is reported that rosiglitazone is a potential neuroprotectant for retinal cells and may increase the retinal cell survival40. It may also delay the onset of proliferative diabetic retinopathy41.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, rosiglitazone-PPAR-γ protects against hypoxia-and oxidant-induced apoptosis by attenuating reactive oxygen species (ROS) production and thereby controls premitochondrial apoptotic targets [11]. Furthermore, PPAR-γ agonists mediate the transcription of superoxide dismutase (SOD) and catalase genes, PPRE sites were found at the promoter region of these two genes, and their upregulation is reversed by the PPAR-γ antagonist GW9662, while PPAR-γ agonists downregulate the expression of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [56][57][58][59]. SOD and catalase are known free radical scavengers, while NADPH oxidase is a ROS generator.…”
Section: Ppar-γ and Post-ischemic Apoptosismentioning
confidence: 98%
“…Troglitazone treatment, another antidiabetic and anti-inflammatory drug, results in decreased expression of HNF4A and SOD2 mRNAs in cellular models (Lauer, et al, 2009,Ruan, et al, 2003. In addition, gliclazide treatment, an oral sulfonylurea hypoglycemic agent, results in decreased protein expression of SOD2 (Onozato, et al, 2004), and rosiglitazone, an insulin sensitizer, increased SOD2 protein expression in retinal cells from mice (Doonan, et al, 2009). Based on these observations, expression of HNF4A and SOD2 in blood may be useful to evaluate the therapeutic effect of anti-diabetic drugs in PD patients.…”
Section: Discussionmentioning
confidence: 99%